A study on the factors affecting student motivation in physical learning among UTAR students - Cheam, Angeline Ching Ie; Chia, Khai Xin; Lee, Ker Xin; Lee, Min Yee (2024)
Effective physical education instructors play a vital role in motivating students. This study investigates the factors influencing student motivation in physical learning within the context of University Tunku Abdul Rahman (UTAR). With the introduction student motivation in physical learning, it has far-reaching implications for university management. Consequently, the primary purpose of this study is to investigate and comprehend factors affecting student motivation in physical learning among UTAR students. This investigation explores strategies and initiatives that university management can implement to enhance student motivation. The study aimed to accomplish the following objectives in particular: To examine the significant impact of family motivational climate on student motivation in physical learning and to examine the significant impact of classroom environment on student motivation in physical learning. Accomplishing these objectives can serve as a valuable resource to university management which can provide valuable insights into the specific factors that drive or hinder student motivation in physical learning. The study investigates aspects like the impact of family motivational climate and classroom environment. These aspects are crucial in figuring out targeted strategies for the university management to improve student motivation. 377 UTAR students who are studying in Kampar and Sungai Long campuses are responders in this study. A questionnaire was used as the research method for this investigation. The Statistical Package for Social Science (SPSS) is used to assess the data that has been gathered.